A review of argasid ticks and associated pathogens of China - Chen, Ze; Liu, Jingze (Frontiers in Veterinary Science, 2022)
It has been recorded 221 species of soft ticks in the world. However, the classification system of Argasidae is still unclear with nearly two-third controversial species in genus level. Therefore, comprehensive research is still necessary. In 2016, Wen and Chen overviewed the valid species of soft ticks in China for the first time. Up to now, the soft tick fauna of China remains poorly known. Although several studies have been undertaken, the information regarding soft ticks and associated diseases are fragmentary. To facilitate the future study of this group, the scattered information on soft ticks of China is herein synthesized. Toward the end of 2021, 15 valid species of argasid ticks have been reported, of these, 9 species (60%) including Argas beijingensis, A. japonicus, A. persicus, A. sinensis, A. vespertilionis, A. vulgaris, Ornithodoros lahorensis, O. tartakovskyi, and O. papillipes have been recorded biting humans. Argas persicus is the most common species, and its borne pathogens are widely investigated, while most other argasid ticks are not sufficiently studied in China. Here, we summarize detailed information regarding hosts, geographical distribution, molecular data, and vector roles of argasid ticks in China.